Luxembourg : Selected Issues-Prospects of the Financial Sector-Tax Harmonization and Asset Market Valuation. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper presents a short history of the development of the financial sector of Luxembourg, highlighting the strong influence of tax and regulatory advantages for its past development. It describes the structure of the banking sector today and summarizes plans for harmonizing the taxation of cross-border interest income that could potentially challenge the future development of the sector. The paper also explains the mechanisms of growth that may have been at work in Luxembourg's financial sector.